The Effect of the Problem Based Learning Model on Critical Thinking Skills in the IPAS Subject for Fifth Grade Elementary School Students - Anjelina, Aulia; Mustika, Dea (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the low critical thinking skills of students in the Natural and Social Science (IPAS) learning, which is caused by conventional learning methods that have not encouraged students to actively think deeply. The aim of this study is to determine the effect of the Problem Based Learning (PBL) model on the critical thinking skills of fifth-grade students at SD IT Bunayya Pekanbaru. This study uses a quantitative approach with a One Group Pretest-Posttest design. The subjects of this study were 30 fifth-grade students from Uwais class at SD IT Bunayya Pekanbaru. The research instruments consisted of multiple-choice test sheets and an observation sheet to assess the implementation of learning using the PBL model. The results of the study show that the average pretest score for students' critical thinking skills was 59.17, which increased to 79.67 in the posttest. Additionally, a significance value of 0.000 < 0.05 was obtained, indicating that the Problem Based Learning model had a significant effect on the critical thinking skills in the IPAS subject for fifth-grade students at SD IT Bunayya Pekanbaru. Observations of the PBL model implementation showed an average implementation rate above 93%, indicating that the learning stages were carried out effectively. It can be concluded that the implementation of the Problem Based Learning model significantly improves students' critical thinking skills and supports a more meaningful and interactive IPAS learning process.